2013
DOI: 10.1603/en12341
|View full text |Cite
|
Sign up to set email alerts
|

The Redbay Ambrosia Beetle (Coleoptera: Curculionidae: Scolytinae) Uses Stem Silhouette Diameter as a Visual Host-Finding Cue

Abstract: The redbay ambrosia beetle (Xyleborus glabratus Eichhoff) is an invasive pest and vector of the pathogen that causes laurel wilt disease in Lauraceous tree species in the eastern United States. This insect uses olfactory cues during host finding, but use of visual cues by X. glabratus has not been previously investigated and may help explain diameter-related patterns in host tree mortality. The objective of this study was to determine whether X. glabratus females visually detect silhouettes of tree stems durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 36 publications
3
36
0
Order By: Relevance
“…It is uncertain whether smaller individuals or resprouts will remain. Mayfield and Brownie (2013) have shown experimentally that the redbay ambrosia beetle visually cues on large-diameter stems, and that may partially explain the greater survival rates of smaller individuals seen in some studies. The basal sprouting of swamp bays possibly will allow existing genets to survive for an extended period, much like the American chestnut continues to survive as small resprouts several decades after all mature trees were killed (Freinkel, 2007).…”
Section: Prognosis For Swamp Bay and Everglades Tree Islandsmentioning
confidence: 90%
“…It is uncertain whether smaller individuals or resprouts will remain. Mayfield and Brownie (2013) have shown experimentally that the redbay ambrosia beetle visually cues on large-diameter stems, and that may partially explain the greater survival rates of smaller individuals seen in some studies. The basal sprouting of swamp bays possibly will allow existing genets to survive for an extended period, much like the American chestnut continues to survive as small resprouts several decades after all mature trees were killed (Freinkel, 2007).…”
Section: Prognosis For Swamp Bay and Everglades Tree Islandsmentioning
confidence: 90%
“…Leaf volatiles potentially could be used by X. glabratus as a long-range cue, or a cue indicating the presence of redbay in the foraging area. Following this long-range attraction through leaf volatiles, tree selection might be mediated through visual rather than olfactory cues, as X. glabratus are known to be attracted by artificial stems of larger diameter (Mayfield and Brownie 2013). Additionally, bark requires damage for volatile release, and once on the tree, the beetles will subsequently determine if the host is suitable for colonization and reproduction, guiding the decision to bore into the wood (Kendra et al 2014a;Kuhns et al 2014a).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated experimentally that females indeed utilize stem diameter as a host-seeking cue [41], but this visual signal only synergizes attraction when in the proper chemical context. Thus, X. glabratus does not bore into trunks/branches of suitable diameter if they lack the appropriate chemical cues (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Test 1 was conducted at the Royce Ranch Unit (N 27°38′410″, W 81°34′307″) from 24 September to 12 November 2010 (7-wk test), and evaluated attraction to five species of Lauraceae: redbay, swampbay, silkbay, avocado, and lancewood. In addition, the test included two controls, consisting of an unbaited trap (to assess random background captures) and a trap baited with live oak (a non-host bolt treatment, to assess potential captures resulting from visual cues [41]). Test 2 was conducted at the Highlands Park Estates (N 27°21′032″, W 81°19′837″) from 4 August to 15 September 2011 (6-wk test), and compared captures of X. glabratus with bolts of camphor tree, sassafras, northern spicebush, California bay laurel, silkbay (an internal control for comparison with results from test 1), and an unbaited trap.…”
Section: Methodsmentioning
confidence: 99%